The Influence of Training, Motivation, and Job Satisfaction on Employee Performance at PT. Parkland World Indonesia - Nurhastuti, Bella; Marzuki, Faisal; Sumardjo, Mahendro; Supriadi, Yudi Nur (Garuda Prestasi Nusantara Consulting, 2022)
This research aims to determine, analyze and prove the influencet of training, motivation, and employee satisfaction on employee performance at PT Parkland World Indonesia. In this research, the sample population was taken from field workers, totaling 2300 workers, all of these workers were staff of Human Resource, General Affairs, PPIC, Export, Marketing, Accounting, Purchasing, Development, Quality Control, Line, Cell Production, Technichal Bottom, Stock Fittings, Warehouse Materials, and Engineering. Based on the criteria for the SEM test requirements, the number of samples taken is 200 samples. The number of samples is close to the number of stock fitting employees, which means that what will be studied further are employees who are in stock fittings. The data analysis technique used is path analysis and hypothesis testing in this study is used Partial Test (t test) and Coefficient of Determination Test using SPSS program. The results obtained from the data analysis of this study explained that there was a positive influence on training, motivation, job satisfaction on employee performance after the research was made a mediating variable. Keywords : training, motivation, job satisfaction, employee performance